"Invisible bias" in the single particle soot photometer due to trigger deadtime. Issue 7 (3rd July 2022) - Schwarz, Joshua. P.; Katich, J. M.; Lee, S. L.; Thomson, D. S.; Watts, L. A.
Abstract: The Single Particle Soot Photometer (SP2) is an instrument for quantifying the refractory black carbon (rBC) mass and microphysical properties of individual aerosol particles. Under substantial aerosol loadings, the SP2 data system can bias rBC concentration measurements low by 40% at a particle rate of 25, 000 particles s −1, with significant bias (∼4%) even at only ∼2000 particles s −1 without any explicit record of this "invisible" effect. Here we present information about the SP2 algorithm for storing individual particle data and its susceptibility to generating this bias, which is strongly sensitive to user choices of various SP2 operational parameters. A method to directly measure this bias, and an approach to assessing it from analysis of saved data is provided, and evaluated with laboratory-generated aerosol and against theory. Finally, recommendations for sampling aerosol and quality-assuring stored SP2 data with this bias in mind are provided. Copyright © 2022 American Association for Aerosol Research